Further Flattening of a Degraded, Turbid Reef System Following a Severe Coral Bleaching Event - Bauman, Andrew G.; Januchowski–Hartley, Fraser A.; Teo, Aaron; Todd, Peter A. (Frontiers in Marine Science, 2022)
Increasing incidence of severe coral bleaching events caused by climate change is contributing to extensive coral losses, shifts in species composition and widespread declines in the physical structure of coral reef ecosystems. With these ongoing changes to coral communities and the concomitant flattening of reef structural complexity, understanding the links between coral composition and structural complexity in maintaining critical ecosystem functions and processes is of critical importance. Here, we documented the impacts of the 2016 global-scale coral bleaching event on seven coral reefs in Singapore; a heavily degraded, turbid reef system. Using a combination of field-based surveys, we examined changes in coral cover, composition and structural complexity before, during and after the 2016 bleaching event. We also quantified differential bleaching-responses and mortality among coral taxa and growth forms using a bleaching response index. Elevated SSTs induced moderate to severe coral bleaching across reefs in Singapore in July 2016, but low overall coral mortality (~12% of colonies). However, we observed high bleaching prevalence and post-bleaching mortality of the three most abundant coral genera (Merulina, Pachyseris and Pectinia), all generalists, declined significantly across reefs between March and November 2016. Four months post-bleaching (November 2016), small-scale structural complexity declined across all Singaporean reefs and ¬no moderately complex reefs remained. Importantly, reductions in structural complexity occurred across reefs with a large range of live coral cover (19–62%) and was linked to the loss of dominant coral genera with low-profile foliose-laminar growth forms which resulted in flatter, less structurally complex reefs across Singapore. And while generalist coral taxa remain highly competitive within Singapore’s reef environment, they may not have the capacity to maintain structural complexity or ensure the persistence of other reef functions, even within communities with high coral cover. The widespread loss of structurally complexity on Singapore’s degraded coral reefs may further impair ecosystem functioning, potentially compromising the long-term stability of reef biodiversity and productivity.